Factors Affecting the Effectiveness and Efficiency of Employees at STMIK Pelita Nusantara - Sirait, Emmy Hotparsaulian; John F. Marpaung (SEAN Institute, 2022)
To enforce discipline, it is not enough just by threats, but it needs balance, namely a sufficient level of welfare. Even so, in fact, discipline is not only determined by the welfare factor, but there are many other factors, it also needs a continuous habit. Based on the preliminary research that has been carried out at STMIK Pelita Nusantara, the problems faced can be formulated as follows